2008
DOI: 10.1175/2007jhm944.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TRMM Multisatellite Precipitation Analysis (TMPA) and Its Utility in Hydrologic Prediction in the La Plata Basin

Abstract: Satellite-based precipitation estimates with high spatial and temporal resolution and large areal coverage provide a potential alternative source of forcing data for hydrological models in regions where conventional in situ precipitation measurements are not readily available. The La Plata basin in South America provides a good example of a case where the use of satellite-derived precipitation could be beneficial. This study evaluates basinwide precipitation estimates from 9 yr (1998)(1999)(2000)(2001)(2002)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
290
0
14

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(326 citation statements)
references
References 48 publications
14
290
0
14
Order By: Relevance
“…It can be observed that the greatest differences occur at the edges of the study area where there are fewer raingauges. This follows the findings reported in Su et al (2008), which ensures that TRMM 3B43.v6 data tend to provide slightly larger estimates than that provided by the raingauge data; this difference is interpreted as mostly reflecting the climatological undercatch correction applied to TRMM data (Huffman et al, 2007). Figure 3 shows the scattergram of precipitation from averaged raingauges data and TRMM 3B43.v6 estimates for spring 1998.…”
Section: Sample Datasupporting
confidence: 82%
See 1 more Smart Citation
“…It can be observed that the greatest differences occur at the edges of the study area where there are fewer raingauges. This follows the findings reported in Su et al (2008), which ensures that TRMM 3B43.v6 data tend to provide slightly larger estimates than that provided by the raingauge data; this difference is interpreted as mostly reflecting the climatological undercatch correction applied to TRMM data (Huffman et al, 2007). Figure 3 shows the scattergram of precipitation from averaged raingauges data and TRMM 3B43.v6 estimates for spring 1998.…”
Section: Sample Datasupporting
confidence: 82%
“…For more than a decade, to the data measured by meteorological observatories, complementary information coming from other instruments (e.g., remote sensing from satellite, radar maps and information from lighting detection systems) can be added (see for example, New et al, 2001;Islam et al, 2002;Su et al, 2008). We have considered the possibility to fill the temporary series by means of the TRMMbased precipitation estimates, which are available for the research community at the following web site: http://daac.gsfc.nasa.gov/data/datapool/TRMM/01 Data Products/02 Gridded/index.html.…”
Section: Sample Datamentioning
confidence: 99%
“…Precipitation data plays the key role in drought monitoring. Rain gauges are the mainly measuring methods for precipitation but they are concentrated in developed countries and are spare in developing countries and remote areas in the world (Adler et al, 2003;Su et al, 2008). Chiu indicated that remote sensing techniques using space-borne sensors provide an excellent complement to continuous monitoring of rain events both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical Precipitation Measuring Mission (TRMM) carrying sensors on precipitation (Kummerow et al, 1998) provides the opportunity for fine spatial-temporal precipitation products. Since the launch of TRMM, there were numerous efforts to evaluate TRMM precipitation products (Bowman, 2005;Chiu et al, 2008;Chiu et al, 2006;Islam et al, 2007;Nair et al, 2009;Nicholson et al, 2003;Rahman et al, 2007;Su et al, 2008;Su et al, 2011;Wong et al, 2008). The accuracy of the version-6 TRMM Multisatellite precipitation analysis (TMPA) is the best among TRMM precipitation products.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the utility of TRMM datasets in estimating rainfall for hydrological modelling of medium-sized and large catchments (e.g. Hong et al 2007;Su et al 2008;Nikolopoulos et al 2013;Yong et al 2012). Less testing has been undertaken in smaller catchments (less than 100 km 2 ).…”
Section: Rainfall Data and Spatial Modellingmentioning
confidence: 99%